Synthesis of Biologically Active Heterocycles via a Domino Sequence Involving an SN2/Thorpe–Ziegler Reaction Step - Larionova, Natalia A.; Shestopalov, Anatoliy M.; Rodinovskaya, Lyudmila A.; Zubarev, Andrey A. (Synthesis, 2021)
This review highlights methods for the synthesis of five- and six-membered heterocycles and their annulated analogues. These methods are based on anionic domino reactions that have a common step: an SN2/Thorpe–Ziegler reaction. In addition, data on the biological activity of these heterocycles are summarized.1 Introduction2 Synthesis of Thiophenes, Pyrroles, Furans and Other Heterocycles2.1 Synthesis of 3-Aminothiophenes2.2 Synthesis of 3-Aminopyrroles2.3 Synthesis of 3-Aminofurans3 Synthesis of Bicyclic Heterocyclic Systems3.1 Thiophenes, Pyrroles and Furans Fused with Five-Membered Heterocycles3.2 Thiophenes, Pyrroles and Furans Fused with Six-Membered Heterocycles4 Synthesis of Heterocyclic Compounds Using Three-Step Domino Reactions5 Synthesis of Heterocyclic Compounds Based on a Combination of Two Domino Reactions6 Miscellaneous7 Conclusion
Keywords: domino reactions; heterocycles; medicinal chemistry; drug discovery; Thorpe–Ziegler reaction